EDUTAINMENT, STRATEGI MENINGKATKAN KREATIFITAS ANAK USIA DINI - Husnul Bahri (Nuansa : Jurnal Studi Islam dan Kemasyarakatan, 2017)
Improving the creativityof early childhood is a from of growth  and  development children’s intelligence, it is importan to start the process preparation in the form human resources from an early age which is the embryo a strong generation that  will become a life in the future. Effort are done by the learning process in early childhood, requires the professionalism of educator who master the various strategies of early childhood learning in accordance with the level of growt and development. Positive responses that will be touched as a stimulans for the development of creativity and brain development. One appropriate strategy is the concept learning based on edutainment. In the concept edutain- ment there are learning theories that are full of ideas for conducing fun learning activities. Learning based edutainment is the key to improving the creativity young children